Uniform heat treatment process for neodymium-iron-boron permanent magnet material

By using plasma and magnetic field generators in the tempering heat treatment of neodymium iron boron magnets, combined with fluorinated carbon nanotubes and ultrasonic preheating technology, the problem of uneven heat receiving of neodymium iron boron magnets in the heat treatment is solved, which significantly improves its Coercive force.

CN119132772AActive Publication Date: 2024-12-13JIANGXI YG MAGNET CO LTD

Patent Information

Application Number
CN202411054954.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2024-12-13
Estimated Expiration
2044-08-02

AI Technical Summary

Technical Problem

In the existing neodymium iron boron magnet tempering heat treatment process, uneven temperature in the furnace leads to uneven heat receiving of the neodymium iron boron magnet during the heat treatment process, affecting the coercive force of its magnet.

Method used

A uniform heat treatment process for neodymium iron boron permanent magnet material is adopted. By using plasma and magnetic field generator in a tempering furnace, the heat is evenly distributed, and combined with carbon fluorinated nanotubes and ultrasonic preheating technology, the magnets are uniformly heated at low temperatures. Heat.

Benefits of technology

The coercive force of the NdFeB permanent magnet material is improved, ensuring uniform heat exposure of the magnet during the heat treatment process, and enhancing magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119132772A_ABST
    Figure CN119132772A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of heat treatment of neodymium-iron-boron permanent magnet materials, in particular to a uniform heat treatment process of a neodymium-iron-boron permanent magnet material. The invention discloses a uniform heat treatment process for a neodymium iron boron permanent magnet material. The uniform heat treatment process comprises the following steps: preparing fluorinated carbon nanotubes; preparing permanent magnet powder containing the fluorinated carbon nanotubes; ultrasonic preheating of the permanent magnet powder; and performing uniform heat treatment on the permanent magnet. In the tempering heat treatment process of the sintered magnetic block, the tempering furnace is filled with the plasmas with good heat conductivity, the magnetic field generated by the magnetic block is offset through the magnetic field generation device, the influence of the magnetic field on distribution of the plasmas is prevented, and therefore the plasmas are evenly distributed in the tempering furnace; and when part of the heating burners are started to carry out low-temperature tempering treatment on the magnetic block, heat can be uniformly distributed in the tempering furnace through plasmas, so that the magnetic block is uniformly heated, and the coercivity of the neodymium iron boron permanent magnet material is better improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat treatment of NdFeB permanent magnet materials, in particular to a uniform heat treatment process of NdFeB permanent magnet materials. Background Art

[0002] NdFeB is a tetragonal crystal formed by neodymium, iron and boron. It is widely used in motors, human magnetic resonance imaging, communications and other fields due to its extremely high magnetism and high coercivity. It is the most commonly used rare earth magnet today.

[0003] NdFeB is divided into two types: sintered NdFeB and bonded NdFeB. Sintered NdFeB is prepared by batching, smelting, powder making, pressing, sintering and tempering heat treatment and subsequent processing. Sintering and tempering heat treatment is the most critical step in the process of preparing sintered NdFeB. Tempering heat treatment of sintered NdFeB magnets can greatly improve their coercive force.

[0004] The existing tempering heat treatment process for NdFeB magnets usually places the sintered NdFeB magnets in a tempering furnace and directly heats them through the burners in the tempering furnace, which can adjust the furnace temperature faster and more conveniently. However, when the tempering furnace is heated at a low temperature, only a part of the burners are started to heat the furnace, and the gaps between the opened burners become larger. In addition, since the burners are installed on the furnace wall, the local temperature of the steel plate is too high, resulting in uneven temperature in the furnace, so that the NdFeB magnets are heated unevenly during the heat treatment process, affecting the heat treatment effect of the NdFeB magnets.

[0005] In order to solve the above process difficulties, the present invention studies a uniform heat treatment process for NdFeB permanent magnet materials, which can make the NdFeB magnets be heated uniformly during the heat treatment process, thereby better improving the coercive force of the magnets. Summary of the invention

[0006] In order to solve the above technical defects, the present invention studies a uniform heat treatment process for NdFeB permanent magnet materials, which can make the NdFeB magnets be heated uniformly during the heat treatment process, thereby better improving the coercive force of the magnets.

[0007] A uniform heat treatment process for NdFeB permanent magnet material comprises the following steps:

[0008] S1: Preparation of fluorinated carbon nanotubes

[0009] A funnel is installed at the upper part of the container, and the funnel can control the falling speed of the powder in the funnel. The carbon nanotubes are placed in the funnel, and the container is closed after the carbon tetrafluoride gas is introduced. The container is heated at high temperature for a period of time, and the funnel is opened at the same time to make the carbon nanotubes fall slowly. The obtained solid powder is cooled to obtain fluorinated carbon nanotubes.

[0010] S2: Preparation of permanent magnet powder

[0011] Nd, Fe, Dy, Cu and B are mixed evenly, and then smelted to obtain an alloy melt, the alloy melt is cast to obtain a permanent magnet ingot, the permanent magnet ingot is subjected to microwave heating and hydrogen crushing together with a catalyst, the crushed ingot is taken out after standing to obtain permanent magnet particles, the permanent magnet particles and fluorinated carbon nanotubes are put into an air flow mill for air flow grinding to obtain permanent magnet powder;

[0012] S3: Ultrasonic preheating of permanent magnet powder

[0013] The permanent magnetic powder, solvent and surfactant are mixed and added into a container to obtain a mixture, the mixture in the container is heated and stirred to obtain a homogeneous solution, the container containing the homogeneous solution is placed into an ultrasonic generator, and the homogeneous solution is ultrasonically heated. The homogeneous solution is heated under ultrasonic treatment, and the solvent evaporates until only solid powder remains in the homogeneous solution, and the preheated permanent magnetic powder is collected;

[0014] S4: Uniform heat treatment of permanent magnets

[0015] The preheated permanent magnetic powder is placed in a mold, and a strong magnetic field is applied to make it directionally pressed between the plates to obtain a material block. The material block is isostatically pressed to obtain a briquette. The briquette is sintered at high temperature and then placed in a tempering furnace for high temperature tempering to obtain a high temperature tempered magnetic block. The plasma generator is started to introduce plasma into the tempering furnace. When the plasma content reaches a certain value, the tempering furnace is closed, and a magnetic field generating device is placed near the tempering furnace. After eliminating the magnetic field of the magnetic block, the magnetic block is low-temperature heated and cooled to obtain a NdFeB permanent magnetic material.

[0016] Furthermore, the preparation of fluorinated carbon nanotubes in step S1 comprises the following steps:

[0017] S1.1: A funnel is installed at the upper part of a container, and the funnel can control the falling speed of the powder in the funnel. 5-6 portions of carbon nanotubes are placed in the funnel, and carbon tetrafluoride gas is introduced so that the content of carbon tetrafluoride accounts for 90-95% of the total content of the gas in the container. The container is sealed to obtain a closed container;

[0018] S1.2: Place the closed container in a muffle furnace and heat it at 600-650°C for 20-25 minutes. At the same time, open the funnel to allow the carbon nanotubes to fall to the bottom of the container within 20-25 minutes. Take out the obtained solid powder and cool it naturally for 1.5-2 hours to obtain fluorinated carbon nanotubes.

[0019] Furthermore, step S2 prepares a permanent magnetic powder containing fluorinated carbon nanotubes, comprising the following steps:

[0020] S2.1: 25-27 parts of Nd, 60-62 parts of Fe, 1.3-1.5 parts of Dy, 0.9-1.1 parts of Cu and 1-1.2 parts of B are mixed and placed in a vacuum suspension furnace for smelting to obtain an alloy melt, and then the alloy melt is poured into a water-cooled copper mold to obtain a permanent magnet ingot;

[0021] S2.2: Place the permanent magnet ingot in an industrial micro furnace and perform microwave heating at a temperature of 200-220°C for 15-20 minutes, place the microwave-heated permanent magnet ingot and 6-7 parts of catalyst in a hydrogen crushing furnace, introduce hydrogen to make the pressure in the furnace 10-12Mpa, adjust the temperature to 350-400°C, perform hydrogen crushing on the ingot for 20-25 minutes, then stop heating and let it stand for 2-3 hours, take out the crushed ingot, and obtain permanent magnet particles;

[0022] S2.3: Place the permanent magnetic particles and 5-7 parts of fluorinated carbon nanotubes into a jet mill, adjust the jet mill power to 200-250kw, and the gas consumption to 30-35m 3 / minute, the gas pressure is 0.7-0.8Mpa, and the permanent magnetic particles and fluorinated carbon nanotubes are mixed and jet-milled for 25-30 minutes to obtain permanent magnetic powder.

[0023] Furthermore, step S3 of ultrasonic preheating the permanent magnet powder comprises the following steps:

[0024] S3.1: Add permanent magnetic powder, 200-220 parts of solvent and 15-20 parts of surfactant into a container to obtain a mixture, adjust the temperature to 40-45°C and the rotation speed to 200-220 rpm to stir the mixture in the container for 40-45 minutes to obtain a homogeneous solution;

[0025] S3.2: Place the container containing the homogeneous solution into an ultrasonic generator, adjust the ultrasonic frequency to 25-28KHz, and ultrasonically heat the homogeneous solution. The homogeneous solution heats up under ultrasonic treatment, and the solvent evaporates until only solid powder remains in the homogeneous solution, and the preheated permanent magnetic powder is collected.

[0026] Furthermore, step S4, uniform heat treatment of the permanent magnet, comprises the following steps:

[0027] S4.1: placing the preheated permanent magnetic powder in a mold, applying a strong magnetic field, directionally pressing the preheated permanent magnetic powder between the plates to obtain a material block, immersing the material block in a cold isostatic press under great pressure for isostatic pressing to obtain a briquette;

[0028] S4.2: placing the pressed block in a vacuum sintering furnace, sintering at a temperature of 1100-1200°C for 3-3.5 hours to obtain a sintered magnetic block, placing the sintered magnetic block in a tempering furnace, starting the heating burner, heating the furnace at a temperature of 850-900°C for 55-60 minutes, and obtaining a high-temperature tempered magnetic block;

[0029] S4.3: Start the plasma generator, adjust the power to 0.5-0.6MW, and introduce plasma into the tempering furnace until the plasma content in the tempering furnace reaches 90-95%, close the tempering furnace, place a magnetic field generating device near the tempering furnace, adjust the direction of the magnetic field to be opposite to the magnetic field generated by the high-temperature tempered magnetic block, and adjust the magnetic field strength until the compass is observed to point accurately to the south, eliminate the magnetic field of the magnetic block, start the heating burner, heat at a temperature of 475-500℃ for 1-1.5 hours, and then water quench the obtained low-temperature tempered magnetic block to room temperature to obtain NdFeB permanent magnet material.

[0030] Furthermore, the catalyst in step S2.2 is aluminum oxide.

[0031] Furthermore, the gas used for jet milling in step S2.3 is nitrogen.

[0032] Furthermore, the surfactant in step S3.1 is sodium dodecylbenzene sulfonate.

[0033] Furthermore, in step S3.1, the material of the container is ceramic.

[0034] Furthermore, the solvent in step S3.1 is acetone.

[0035] The beneficial effects are: 1. In the process of tempering heat treatment of the sintered magnetic blocks, the present invention first performs normal high-temperature tempering treatment on the magnetic blocks, and then fills the tempering furnace with plasma with good thermal conductivity, and offsets the magnetic field generated by the magnetic blocks through a magnetic field generating device to prevent the magnetic field from affecting the distribution of plasma, thereby making the plasma evenly distributed in the tempering furnace. When some heating burners are started to perform low-temperature tempering treatment on the magnetic blocks, the heat can also be evenly distributed in the tempering furnace through the plasma, so that the magnetic blocks are evenly heated, and the coercive force of the NdFeB permanent magnet material is better improved.

[0036] 2. The present invention obtains fluorinated carbon nanotubes by fluorinating carbon nanotubes, and adds fluorinated carbon nanotubes during the air flow milling of permanent magnetic particles to fully mix the two and obtain permanent magnetic powder with a smaller particle size. C and F elements are introduced into the subsequently prepared magnetic blocks to enhance the thermal conductivity of the magnetic blocks, so that the magnetic blocks can be better and more evenly heated during the heat treatment process, thereby improving the coercive force of the NdFeB permanent magnetic material.

[0037] 3. The present invention controls the falling speed of carbon nanotube powder through a funnel, so that it slowly falls from the top in a container filled with carbon tetrafluoride, and applies high temperature to allow the carbon nanotube powder to fully contact and react with carbon tetrafluoride gas, thereby increasing the output rate of fluorinated carbon nanotubes.

[0038] 4. The present invention disperses the permanent magnetic powder evenly in the solvent and then ultrasonically heats the homogeneous solution until the solvent evaporates, thereby greatly reducing the inhomogeneous phase α-Fe in the obtained permanent magnetic powder, reducing the stress between the components in the powder, making the distribution of the components in the powder more uniform, and making the magnetic blocks more evenly heated in the subsequent heat treatment, thereby improving the coercive force of the NdFeB permanent magnetic material.

[0039] 5. The present invention first performs microwave heating treatment on the permanent magnet ingot to make the molecules of the permanent magnet ingot more active and enhance its surface activity, and adds a catalyst during the hydrogen crushing process to improve the subsequent binding ability of hydrogen and the permanent magnet ingot, thereby improving the effect of hydrogen crushing and obtaining permanent magnet particles with smaller particle size. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The present invention is a flowchart of a uniform heat treatment process for NdFeB permanent magnet materials used in an embodiment of the present invention.

[0041] Figure 2 This is a table comparing the coercive forces of the NdFeB permanent magnet material prepared by the embodiment of Comparative Example 1 of the present invention and the NdFeB permanent magnet material prepared by the conventional process for preparing NdFeB magnets.

[0042] Figure 3 This is a table comparing the coercive forces of the NdFeB permanent magnet material prepared in the embodiment of Comparative Example 2 of the present invention and the NdFeB permanent magnet material prepared without adding fluorinated carbon nanotubes.

[0043] Figure 4 This is a table comparing the coercive forces of the NdFeB permanent magnet material prepared in the embodiment of Comparative Example 1 of the present invention and the NdFeB permanent magnet material prepared in Comparative Example 3 without the operation of introducing plasma into the tempering furnace and eliminating the magnetic field.

[0044] Figure 5 This is a table comparing the coercive forces of the NdFeB permanent magnet material prepared in the embodiment of Comparative Example 2 of the present invention and the NdFeB permanent magnet material prepared by removing step S3.

[0045] Figure 6 This is a table comparing the quality of permanent magnet particles obtained by hydrogen crushing the permanent magnet ingots in Comparative Example 5 of the present invention and passing through a 100-mesh sieve.

[0046] Figure 7This is a table comparing the fluorine atom content after the reaction of carbon nanotubes and carbon tetrafluoride when a funnel is provided and when a funnel is not provided in Comparative Example 6 of the present invention. DETAILED DESCRIPTION

[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Example 1

[0049] A uniform heat treatment process for NdFeB permanent magnet materials, such as Figure 1 As shown, the following steps are included:

[0050] S1: Preparation of fluorinated carbon nanotubes

[0051] S1.1: A funnel is installed at the top of a container, and the funnel can control the falling speed of the powder in the funnel. Five portions of carbon nanotubes are placed in the funnel, and carbon tetrafluoride gas is introduced so that the content of carbon tetrafluoride accounts for 90% of the total content of the gas in the container. The container is sealed to obtain a closed container;

[0052] S1.2: Place the closed container in a muffle furnace and heat it at 600°C for 20 minutes. At the same time, open the funnel to allow the carbon nanotubes to fall to the bottom of the container within 20 minutes. Take out the obtained solid powder and cool it naturally for 1.5 hours to obtain fluorinated carbon nanotubes. Introduce C and F elements into the magnetic block to enhance the thermal conductivity of the magnetic block, so that the magnetic block can be better and more evenly heated during the heat treatment process, thereby improving the coercive force of the NdFeB permanent magnet material.

[0053] S2: Preparation of permanent magnetic powder containing fluorinated carbon nanotubes

[0054] S2.1: 25 parts of Nd, 60 parts of Fe, 1.3 parts of Dy, 0.9 parts of Cu and 1 part of B are mixed and placed in a vacuum suspension furnace for smelting to obtain an alloy melt, and then the alloy melt is poured into a water-cooled copper mold to obtain a permanent magnet ingot;

[0055] S2.2: The permanent magnet ingot is placed in an industrial micro furnace and microwave heated at 200°C for 15 minutes to improve the subsequent hydrogen-to-permanent magnet ingot bonding ability and improve the efficiency of hydrogen crushing. The microwave-heated permanent magnet ingot and 6 parts of alumina are placed in a hydrogen crushing furnace. Alumina further improves the efficiency of hydrogen crushing. Hydrogen is introduced to make the pressure in the furnace 10Mpa, and the temperature is adjusted to 350°C. The ingot is hydrogen crushed for 20 minutes, and then the heating is stopped and allowed to stand for 2 hours. The crushed ingot is taken out to obtain permanent magnet particles.

[0056] S2.3: Put the permanent magnetic particles and 5 parts of fluorinated carbon nanotubes into the air flow mill, adjust the power of the air flow mill to 200kw, blow in nitrogen, and the gas consumption is 30m 3 / minute, the gas pressure is 0.7Mpa, the permanent magnetic particles and fluorinated carbon nanotubes are jet milled for 25 minutes to obtain permanent magnetic powder.

[0057] S3: Ultrasonic preheating of permanent magnet powder

[0058] S3.1: Mix the permanent magnet powder, 200 parts of acetone and 15 parts of sodium dodecylbenzene sulfonate and add them into a ceramic container to obtain a mixture, adjust the temperature to 40°C and the rotation speed to 200 rpm to stir the mixture in the ceramic container for 40 minutes to obtain a homogeneous solution;

[0059] S3.2: Place the ceramic container containing the homogeneous solution into an ultrasonic generator, adjust the ultrasonic frequency to 25KHz, and perform ultrasonic heating on the homogeneous solution. The homogeneous solution heats up under ultrasonic treatment, and the acetone evaporates until only solid powder remains in the homogeneous solution, thereby greatly reducing the inhomogeneous phase α-Fe in the permanent magnet powder, reducing the stress between the components in the powder, making the distribution of the components in the powder more uniform, and allowing the magnetic block to be better heated evenly in the subsequent heat treatment.

[0060] S4: Uniform heat treatment of permanent magnets

[0061] S4.1: placing the preheated permanent magnetic powder in a mold, applying a strong magnetic field, directionally pressing the preheated permanent magnetic powder between the plates to obtain a material block, immersing the material block in a cold isostatic press under great pressure for isostatic pressing to obtain a briquette;

[0062] S4.2: Place the pressed block in a vacuum sintering furnace and sinter it at 1100°C for 3 hours. Place the obtained sintered magnetic block in a tempering furnace, start the heating burner, and heat the furnace at 850°C for 55 minutes to obtain a high-temperature tempered magnetic block.

[0063] S4.3: Start the plasma generator, adjust the power to 0.5MW, and introduce plasma into the tempering furnace until the plasma content in the tempering furnace reaches 90%, close the tempering furnace, place a magnetic field generating device near the tempering furnace, adjust the direction of the magnetic field to be opposite to the magnetic field generated by the high-temperature tempered magnetic block, and adjust the magnetic field strength until the compass is observed to point accurately to the south, eliminate the magnetic field of the magnetic block, and prevent the magnetic field from affecting the distribution of plasma, so that the plasma is evenly distributed in the tempering furnace. When some heating burners are started to perform low-temperature tempering on the magnetic block, the heat can also be evenly distributed in the tempering furnace through the plasma, so that the magnetic block is evenly heated, and the coercive force of the NdFeB permanent magnet material is better improved. Start the heating burner and heat at 475°C for 1 hour. Then, the obtained low-temperature tempered magnetic block is water quenched and cooled to room temperature to obtain the NdFeB permanent magnet material.

[0064] Example 2

[0065] A uniform heat treatment process for NdFeB permanent magnet materials, such as Figure 1 As shown, the following steps are included:

[0066] S1: Preparation of fluorinated carbon nanotubes

[0067] S1.1: A funnel is installed at the upper part of a container, and the funnel can control the falling speed of the powder in the funnel. Six portions of carbon nanotubes are placed in the funnel, and carbon tetrafluoride gas is introduced so that the content of carbon tetrafluoride accounts for 90% of the total content of the gas in the container. The container is sealed to obtain a closed container;

[0068] S1.2: Place the closed container in a muffle furnace and heat it at 600°C for 20 minutes. At the same time, open the funnel to allow the carbon nanotubes to fall to the bottom of the container within 20 minutes. Take out the obtained solid powder and cool it naturally for 1.5 hours to obtain fluorinated carbon nanotubes. Introduce C and F elements into the magnetic block to enhance the thermal conductivity of the magnetic block, so that the magnetic block can be better and more evenly heated during the heat treatment process, thereby improving the coercive force of the NdFeB permanent magnet material.

[0069] S2: Preparation of permanent magnetic powder containing fluorinated carbon nanotubes

[0070] S2.1: 27 parts of Nd, 62 parts of Fe, 1.5 parts of Dy, 1.1 parts of Cu and 1.2 parts of B are mixed and placed in a vacuum suspension furnace for smelting to obtain an alloy melt, and then the alloy melt is poured into a water-cooled copper mold to obtain a permanent magnet ingot;

[0071] S2.2: The permanent magnet ingot is placed in an industrial micro furnace and microwave heated at 200°C for 15 minutes to improve the subsequent hydrogen-to-permanent magnet ingot bonding ability and improve the efficiency of hydrogen crushing. The microwave-heated permanent magnet ingot and 6 parts of alumina are placed in a hydrogen crushing furnace. Alumina further improves the efficiency of hydrogen crushing. Hydrogen is introduced to make the pressure in the furnace 10Mpa, and the temperature is adjusted to 350°C. The ingot is hydrogen crushed for 20 minutes, and then the heating is stopped and allowed to stand for 2 hours. The crushed ingot is taken out to obtain permanent magnet particles.

[0072] S2.3: Put the permanent magnetic particles and 7 parts of fluorinated carbon nanotubes into the air flow mill, adjust the power of the air flow mill to 200kw, blow in nitrogen, and the gas consumption is 30m 3 / minute, the gas pressure is 0.7 MPa, and the permanent magnetic particles and fluorinated carbon nanotubes are jet milled for 25 minutes to obtain permanent magnetic powder.

[0073] S3: Ultrasonic preheating of permanent magnet powder

[0074] S3.1: Mix the permanent magnet powder, 220 parts of acetone and 20 parts of sodium dodecylbenzene sulfonate and add them into a ceramic container to obtain a mixture, adjust the temperature to 40°C and the rotation speed to 200 rpm to stir the mixture in the ceramic container for 40 minutes to obtain a homogeneous solution;

[0075] S3.2: Place the ceramic container containing the homogeneous solution into an ultrasonic generator, adjust the ultrasonic frequency to 25KHz, and perform ultrasonic heating on the homogeneous solution. The homogeneous solution heats up under ultrasonic treatment, and the acetone evaporates until only solid powder remains in the homogeneous solution, thereby greatly reducing the inhomogeneous phase α-Fe in the permanent magnet powder, reducing the stress between the components in the powder, making the distribution of the components in the powder more uniform, and allowing the magnetic block to be better heated evenly in the subsequent heat treatment.

[0076] S4: Uniform heat treatment of permanent magnets

[0077] S4.1: placing the preheated permanent magnetic powder in a mold, applying a strong magnetic field, directionally pressing the preheated permanent magnetic powder between the plates to obtain a material block, immersing the material block in a cold isostatic press under great pressure for isostatic pressing to obtain a briquette;

[0078] S4.2: Place the pressed block in a vacuum sintering furnace and sinter it at 1100°C for 3 hours. Place the obtained sintered magnetic block in a tempering furnace, start the heating burner, and heat the furnace at 850°C for 55 minutes to obtain a high-temperature tempered magnetic block.

[0079] S4.3: Start the plasma generator, adjust the power to 0.5MW, and introduce plasma into the tempering furnace until the plasma content in the tempering furnace reaches 90%, close the tempering furnace, place a magnetic field generating device near the tempering furnace, adjust the direction of the magnetic field to be opposite to the magnetic field generated by the high-temperature tempered magnetic block, and adjust the magnetic field strength until the compass is observed to point accurately to the south, eliminate the magnetic field of the magnetic block, and prevent the magnetic field from affecting the distribution of plasma, so that the plasma is evenly distributed in the tempering furnace. When some heating burners are started to perform low-temperature tempering on the magnetic block, the heat can also be evenly distributed in the tempering furnace through the plasma, so that the magnetic block is evenly heated, and the coercive force of the NdFeB permanent magnet material is better improved. Start the heating burner and heat at 475°C for 1 hour. Then, the obtained low-temperature tempered magnetic block is water quenched and cooled to room temperature to obtain the NdFeB permanent magnet material.

[0080] Example 3

[0081] A uniform heat treatment process for NdFeB permanent magnet materials, such as Figure 1 As shown, the following steps are included:

[0082] S1: Preparation of fluorinated carbon nanotubes

[0083] S1.1: A funnel is installed at the upper part of a container, and the funnel can control the falling speed of the powder in the funnel. Five portions of carbon nanotubes are placed in the funnel, and carbon tetrafluoride gas is introduced so that the content of carbon tetrafluoride accounts for 95% of the total content of the gas in the container. The container is sealed to obtain a closed container;

[0084] S1.2: Place the closed container in a muffle furnace and heat it at 650°C for 25 minutes. At the same time, open the funnel to allow the carbon nanotubes to fall to the bottom of the container within 25 minutes. Take out the obtained solid powder and cool it naturally for 2 hours to obtain fluorinated carbon nanotubes. Introduce C and F elements into the magnetic block to enhance the thermal conductivity of the magnetic block, so that the magnetic block can be better and more evenly heated during the heat treatment process, thereby improving the coercive force of the NdFeB permanent magnet material.

[0085] S2: Preparation of permanent magnetic powder containing fluorinated carbon nanotubes

[0086] S2.1: 25 parts of Nd, 60 parts of Fe, 1.3 parts of Dy, 0.9 parts of Cu and 1 part of B are mixed and placed in a vacuum suspension furnace for smelting to obtain an alloy melt, and then the alloy melt is poured into a water-cooled copper mold to obtain a permanent magnet ingot;

[0087] S2.2: The permanent magnet ingot is placed in an industrial micro furnace and microwave heated at 220°C for 20 minutes to improve the subsequent hydrogen-to-permanent magnet ingot bonding ability and improve the efficiency of hydrogen crushing. The microwave-heated permanent magnet ingot and 6 parts of alumina are placed in a hydrogen crushing furnace. Alumina further improves the efficiency of hydrogen crushing. Hydrogen is introduced to make the pressure in the furnace 12Mpa, and the temperature is adjusted to 400°C. The ingot is hydrogen crushed for 25 minutes, and then the heating is stopped and allowed to stand for 3 hours. The crushed ingot is taken out to obtain permanent magnet particles.

[0088] S2.3: Put the permanent magnetic particles and 5 parts of fluorinated carbon nanotubes into the air flow mill, adjust the power of the air flow mill to 250kw, blow in nitrogen, and the gas consumption is 35m 3 / minute, the gas pressure is 0.8Mpa, and the permanent magnetic particles and fluorinated carbon nanotubes are jet milled for 30 minutes to obtain permanent magnetic powder.

[0089] S3: Ultrasonic preheating of permanent magnet powder

[0090] S3.1: Mix the permanent magnet powder, 200 parts of acetone and 15 parts of sodium dodecylbenzene sulfonate and add them into a ceramic container to obtain a mixture, adjust the temperature to 45°C and the rotation speed to 220 rpm to stir the mixture in the ceramic container for 45 minutes to obtain a homogeneous solution;

[0091] S3.2: Place the ceramic container containing the homogeneous solution into an ultrasonic generator, adjust the ultrasonic frequency to 28KHz, and perform ultrasonic heating on the homogeneous solution. The homogeneous solution heats up under ultrasonic treatment, and the acetone evaporates until only solid powder remains in the homogeneous solution, thereby greatly reducing the inhomogeneous phase α-Fe in the permanent magnet powder, reducing the stress between the components in the powder, making the distribution of the components in the powder more uniform, and allowing the magnetic block to be better heated evenly in subsequent heat treatment.

[0092] S4: Uniform heat treatment of permanent magnets

[0093] S4.1: placing the preheated permanent magnetic powder in a mold, applying a strong magnetic field, directionally pressing the preheated permanent magnetic powder between the plates to obtain a material block, immersing the material block in a cold isostatic press under great pressure for isostatic pressing to obtain a briquette;

[0094] S4.2: placing the pressed block in a vacuum sintering furnace, sintering at a temperature of 1200°C for 3.5 hours, placing the obtained sintered magnetic block in a tempering furnace, starting the heating burner, heating the furnace at a temperature of 900°C for 60 minutes, and obtaining a high-temperature tempered magnetic block;

[0095] S4.3: Start the plasma generator, adjust the power to 0.6MW, and introduce plasma into the tempering furnace until the plasma content in the tempering furnace reaches 95%. Close the tempering furnace, place a magnetic field generating device near the tempering furnace, adjust the magnetic field direction to be opposite to the magnetic field generated by the high-temperature tempered magnetic block, and adjust the magnetic field strength until the compass is observed to point accurately to the south, eliminate the magnetic field of the magnetic block, and prevent the magnetic field from affecting the distribution of plasma, so that the plasma is evenly distributed in the tempering furnace. When some heating burners are started to perform low-temperature tempering on the magnetic block, the heat can also be evenly distributed in the tempering furnace through the plasma, so that the magnetic block is evenly heated, and the coercive force of the NdFeB permanent magnet material is better improved. Start the heating burner and heat at 500°C for 1.5 hours. Then the obtained low-temperature tempered magnetic block is water quenched and cooled to room temperature to obtain the NdFeB permanent magnet material.

[0096] Comparative Example 1

[0097] Compared with Example 1, the difference of Comparative Example 1 is that Comparative Example 1 is a traditional process flow for preparing NdFeB magnets, specifically, batching, smelting, powder making, pressing, sintering and tempering heat treatment, wherein the tempering heat treatment is to place the NdFeB magnet in a tempering furnace for tempering heat treatment.

[0098] The processes of Example 1, Example 2, Example 3 and Comparative Example 1 were used to prepare Nd, Fe, Dy, Cu and B with the same mass ratio, and three portions of each were prepared. The coercive force of the prepared NdFeB permanent magnet material was measured by the method of "GBT13888-2009 Measuring the coercive force of magnetic materials in an open magnetic circuit", and the data were recorded and tabulated, as shown in FIG. Figure 2 It can be seen that the coercive force of the NdFeB permanent magnet materials prepared in Example 1, Example 2, and Example 3 is higher than that of the NdFeB permanent magnet material prepared in Comparative Example 1, which proves that the process in the embodiment can make the NdFeB magnet evenly heated during the heat treatment process, thereby better improving the coercive force of the magnet.

[0099] Comparative Example 2

[0100] Compared with Example 1, the difference of Comparative Example 2 is that in Comparative Example 2, the permanent magnetic particles and the fluorinated carbon nanotubes are not jet-milled together, and the remaining processes for preparing the NdFeB permanent magnetic material are the same as those in Example 1. The preparation is repeated three times, and the NdFeB permanent magnetic materials prepared in Example 1, Example 2, Example 3 and Comparative Example 2 are measured for their coercive force using the method of "GBT13888-2009 Measurement of coercive force of magnetic materials in open magnetic circuit", and the data are recorded and tabulated, as shown in FIG. Figure 3It can be seen that the coercive force of the NdFeB permanent magnet materials prepared in Example 1, Example 2, and Example 3 is higher than that of the NdFeB permanent magnet material prepared in Comparative Example 2, which can prove that adding fluorinated carbon nanotubes during the casting of permanent magnet ingots can enable the magnetic blocks to be better and more evenly heated during the heat treatment process, thereby improving the coercive force of the NdFeB permanent magnet material.

[0101] Comparative Example 3

[0102] Compared with Example 1, the difference of Comparative Example 3 is that in Comparative Example 3, the operation of introducing plasma into the tempering furnace and eliminating the magnetic field in step S4.3 is removed, and low-temperature tempering is directly performed. The remaining processes for preparing the NdFeB permanent magnet material are the same as those in Example 1. The process of Comparative Example 3 is repeated three times, and the NdFeB permanent magnet material prepared in Comparative Example 3 is measured for its coercive force using the method of "GBT13888-2009 Measuring the coercive force of magnetic materials in an open magnetic circuit", and the data are recorded and tabulated together with the data of Examples 1, 2 and 3 in Comparative Example 1, as shown in FIG. Figure 4 It can be seen that the coercive force of the NdFeB permanent magnet materials prepared in Example 1, Example 2, and Example 3 is higher than that of the NdFeB permanent magnet material prepared in Comparative Example 3, which can prove that introducing plasma into the tempering furnace and eliminating the magnetic field can make the heat evenly distributed in the tempering furnace through the plasma, so that the magnetic block is evenly heated, and the coercive force of the NdFeB permanent magnet material is better improved.

[0103] Comparative Example 4

[0104] Compared with Example 1, the difference of Comparative Example 4 is that step S3 is removed from Comparative Example 4, and the remaining processes for preparing the NdFeB permanent magnet material are the same as those in Example 1. The process of Comparative Example 4 is repeated three times, and the NdFeB permanent magnet material prepared in Comparative Example 3 is measured for its coercive force using the method of "GBT13888-2009 Measuring the coercive force of magnetic materials in an open magnetic circuit", and the data are recorded and tabulated together with the data of Example 1, Example 2 and Example 3 in Comparative Example 2, as shown in FIG. Figure 5 It can be seen that the coercive force of the NdFeB permanent magnet materials prepared in Example 1, Example 2, and Example 3 is higher than that of the NdFeB permanent magnet material prepared in Comparative Example 4, which can prove that ultrasonic preheating of the permanent magnet powder can make the distribution of the components in the powder more uniform, so that the magnetic block can be better heated evenly in the subsequent heat treatment, thereby improving the coercive force of the NdFeB permanent magnet material.

[0105] Comparative Example 5

[0106] Compared with Example 1, the difference of Comparative Example 5 is that in Comparative Example 5, the microwave heating of the permanent magnet ingot and the added alumina in step S2.1 are removed, and the remaining processes for preparing NdFeB permanent magnet materials are the same as those in Example 1. Six portions of 500g of the permanent magnet ingot obtained by Example 1 are taken, and the hydrogen crushing of Example 1 and the hydrogen crushing of Comparative Example 5 are performed three times, respectively. The obtained permanent magnet particles are passed through a 100-mesh sieve to screen out permanent magnet particles with smaller particle sizes. The larger the mass, the better the hydrogen crushing effect. The permanent magnet particles passing through the sieve are weighed and the data are recorded to make a table, as shown in FIG. Figure 6 It can be seen that the content of permanent magnetic particles passing through the 100-mesh sieve obtained in the three examples 1 is more than that in the comparative example 5, which can prove that microwave heating treatment of the permanent magnetic ingot and adding a catalyst during the hydrogen crushing process can improve the subsequent bonding ability of hydrogen and the permanent magnetic ingot, thereby improving the effect of hydrogen crushing.

[0107] Comparative Example 6

[0108] Compared with Example 1, the difference of Comparative Example 6 is that the funnel device is removed in Comparative Example 6, and the carbon nanotubes are directly placed in a container to react with carbon tetrafluoride at a high temperature. The other conditions for preparing fluorinated carbon nanotubes are the same as those in Example 1. The processes of Example 1 and Comparative Example 6 are respectively used to prepare fluorinated carbon nanotubes 5 times, and the content of fluorine atoms in the fluorinated carbon nanotubes is measured by atomic absorption spectrometer and the percentage is calculated. The data are recorded and tabulated, as shown in FIG. Figure 7 It can be seen that the fluorine atom content of the fluorinated carbon nanotubes prepared in Example 1 is higher than that of the fluorinated carbon nanotubes prepared in Comparative Example 6, which can prove that the output rate of fluorinated carbon nanotubes can be increased by dropping the carbon nanotube powder from the top of the container through a funnel.

[0109] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A uniform heat treatment process for NdFeB permanent magnet materials, characterized in that: The following steps are involved: S1: Preparation of fluorinated carbon nanotubes A funnel is installed at the upper part of the container, and the funnel can control the falling speed of the powder in the funnel. The carbon nanotubes are placed in the funnel, and the container is closed after the carbon tetrafluoride gas is introduced. The container is heated at high temperature for a period of time, and the funnel is opened at the same time to make the carbon nanotubes fall slowly. The obtained solid powder is cooled to obtain fluorinated carbon nanotubes. S2: Preparation of permanent magnetic powder containing fluorinated carbon nanotubes Nd, Fe, Dy, Cu and B are mixed evenly, and then smelted to obtain an alloy melt, the alloy melt is cast to obtain a permanent magnet ingot, the permanent magnet ingot is subjected to microwave heating and hydrogen crushing together with a catalyst, the crushed ingot is taken out after standing to obtain permanent magnet particles, the permanent magnet particles and fluorinated carbon nanotubes are put into an air flow mill for air flow grinding to obtain permanent magnet powder; S3: Ultrasonic preheating of permanent magnet powder The permanent magnetic powder, solvent and surfactant are mixed and added into a container to obtain a mixture, the mixture in the container is heated and stirred to obtain a homogeneous solution, the container containing the homogeneous solution is placed into an ultrasonic generator, and the homogeneous solution is ultrasonically heated. The homogeneous solution is heated under ultrasonic treatment, and the solvent evaporates until only solid powder remains in the homogeneous solution, and the preheated permanent magnetic powder is collected; S4: Uniform heat treatment of permanent magnets The preheated permanent magnetic powder is placed in a mold, and a strong magnetic field is applied to make it directionally pressed between the plates to obtain a material block. The material block is isostatically pressed to obtain a pressed block, and the pressed block is sintered at high temperature. The obtained sintered magnetic block is placed in a tempering furnace for high temperature tempering treatment to obtain a high temperature tempered magnetic block, and a plasma generator is started to pass plasma into the tempering furnace. When the plasma content reaches a certain value, the tempering furnace is closed, and a magnetic field generating device is placed near the tempering furnace. After eliminating the magnetic field of the magnetic block, the magnetic block is low-temperature heated, and the NdFeB permanent magnetic material is obtained after cooling.

2. The uniform heat treatment process of NdFeB permanent magnet material according to claim 1, characterized in that: Step S1: Preparation of fluorinated carbon nanotubes, comprising the following steps: S1.1: A funnel is installed at the upper part of a container, and the funnel can control the falling speed of the powder in the funnel. 5-6 portions of carbon nanotubes are placed in the funnel, and carbon tetrafluoride gas is introduced so that the content of carbon tetrafluoride accounts for 90-95% of the total content of the gas in the container. The container is sealed to obtain a closed container; S1.2: Place the closed container in a muffle furnace and heat it at 600-650°C for 20-25 minutes. At the same time, open the funnel to allow the carbon nanotubes to fall to the bottom of the container within 20-25 minutes. Take out the obtained solid powder and cool it naturally for 1.5-2 hours to obtain fluorinated carbon nanotubes.

3. The uniform heat treatment process of NdFeB permanent magnet material according to claim 1, characterized in that: Step S2 prepares a permanent magnetic powder containing fluorinated carbon nanotubes, comprising the following steps: S2.1: 25-27 parts of Nd, 60-62 parts of Fe, 1.3-1.5 parts of Dy, 0.9-1.1 parts of Cu and 1-1.2 parts of B are mixed and placed in a vacuum suspension furnace for smelting to obtain an alloy melt, and then the alloy melt is poured into a water-cooled copper mold to obtain a permanent magnet ingot; S2.2: Place the permanent magnet ingot in an industrial micro furnace and perform microwave heating at a temperature of 200-220°C for 15-20 minutes, place the microwave-heated permanent magnet ingot and 6-7 parts of catalyst in a hydrogen crushing furnace, introduce hydrogen to make the pressure in the furnace 10-12Mpa, adjust the temperature to 350-400°C, perform hydrogen crushing on the ingot for 20-25 minutes, then stop heating and let it stand for 2-3 hours, take out the crushed ingot, and obtain permanent magnet particles; S2.3: Place the permanent magnetic particles and 5-7 parts of fluorinated carbon nanotubes into a jet mill, adjust the jet mill power to 200-250kw, and the gas consumption to 30-35m 3 / minute, the gas pressure is 0.7-0.8Mpa, and the permanent magnetic particles and fluorinated carbon nanotubes are mixed and jet-milled for 25-30 minutes to obtain permanent magnetic powder.

4. The uniform heat treatment process of NdFeB permanent magnet material according to claim 1, characterized in that: Step S3: ultrasonic preheating of permanent magnet powder, comprising the following steps: S3.1: Add permanent magnetic powder, 200-220 parts of solvent and 15-20 parts of surfactant into a container to obtain a mixture, adjust the temperature to 40-45°C and the rotation speed to 200-220 rpm to stir the mixture in the container for 40-45 minutes to obtain a homogeneous solution; S3.2: Place the container containing the homogeneous solution into an ultrasonic generator, adjust the ultrasonic frequency to 25-28KHz, and ultrasonically heat the homogeneous solution. The homogeneous solution heats up under ultrasonic treatment, and the solvent evaporates until only solid powder remains in the homogeneous solution, and the preheated permanent magnetic powder is collected.

5. The uniform heat treatment process of NdFeB permanent magnet material according to claim 1, characterized in that: Step S4: uniform heat treatment of the permanent magnet, comprising the following steps: S4.1: placing the preheated permanent magnetic powder in a mold, applying a strong magnetic field, directionally pressing the preheated permanent magnetic powder between the plates to obtain a material block, immersing the material block in a cold isostatic press under great pressure for isostatic pressing to obtain a briquette; S4.2: Place the pressed block in a vacuum sintering furnace and sinter it at a temperature of 1100-1200°C for 3-3.5 hours. Place the obtained sintered magnetic block in a tempering furnace, start the heating burner, and heat the furnace at a temperature of 850-900°C for 55-60 minutes to obtain a high-temperature tempered magnetic block. S4.3: Start the plasma generator, adjust the power to 0.5-0.6MW, and introduce plasma into the tempering furnace until the plasma content in the tempering furnace reaches 90-95%, close the tempering furnace, place a magnetic field generating device near the tempering furnace, adjust the direction of the magnetic field to be opposite to the magnetic field generated by the high-temperature tempered magnetic block, and adjust the magnetic field strength until the compass is observed to point accurately to the south, eliminate the magnetic field of the magnetic block, start the heating burner, heat at a temperature of 475-500℃ for 1-1.5 hours, and then water quench the obtained low-temperature tempered magnetic block to room temperature to obtain NdFeB permanent magnet material.

6. The uniform heat treatment process of NdFeB permanent magnet material according to claim 3, characterized in that: The catalyst in step S2.2 is alumina.

7. The uniform heat treatment process of NdFeB permanent magnet material according to claim 3, characterized in that: The gas used for jet milling in step S2.3 is nitrogen.

8. The uniform heat treatment process for NdFeB permanent magnet material according to claim 4, characterized in that: The surfactant in step S3.1 is sodium dodecylbenzene sulfonate.

9. The uniform heat treatment process of NdFeB permanent magnet material according to claim 4, characterized in that: The material of the container in step S3.1 is ceramic.

10. The uniform heat treatment process of NdFeB permanent magnet material according to claim 4, characterized in that: The solvent in step S3.1 is acetone.

Citation Information

Patent Citations

  • Preparation method of neodymium iron boron magnet

    CN108417374A

  • Preparation method of magnetic fluorocarbon nanomaterial

    CN109772258A

  • Rare earth permanent magnet

    CN1838343A

  • Method for preparing carbon nanoparticles-polymer composites using magnetic fields and the carbon nanoparticles-polymer composites

    KR1020110037055A

  • Macroscopic ordered assembly of carbon nanotubes

    US6790425B1

Cited By

  • Neodymium-iron-boron magnet for improving magnetic performance based on grain boundary diffusion and preparation method thereof

    CN120977766A

  • Neodymium-iron-boron magnet with improved magnetic properties based on grain boundary diffusion and method for producing same

    CN120977766B